2023
DOI: 10.1186/s13550-023-01011-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of 99mTc-MAA-based dosimetry in personalized 90Y-SIRT planning for liver malignancies

Abstract: Background Selective internal radiation therapy with 90Y radioembolization aims to selectively irradiate liver tumours by administering radioactive microspheres under the theragnostic assumption that the pre-therapy injection of 99mTc labelled macroaggregated albumin (99mTc-MAA) provides an estimation of the 90Y microspheres biodistribution, which is not always the case. Due to the growing interest in theragnostic dosimetry for personalized radionuclide therapy, a robust relationship between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, recent papers supported the current study’s dosimetry planning method and revealed that pre-treatment MAA is strongly correlated with the post-90Y PET, in terms of the mean absorbed dose and also the dose distribution. 22 , 23 Fourthly, the administered sphere count as dose/sphere was not calculated for each patient. The availability of flexible dose shipping options may have resulted in different dose/sphere values for different administrations, resulting in varying sphere density and dose uniformity/heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent papers supported the current study’s dosimetry planning method and revealed that pre-treatment MAA is strongly correlated with the post-90Y PET, in terms of the mean absorbed dose and also the dose distribution. 22 , 23 Fourthly, the administered sphere count as dose/sphere was not calculated for each patient. The availability of flexible dose shipping options may have resulted in different dose/sphere values for different administrations, resulting in varying sphere density and dose uniformity/heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the management of patients treated with selective internal radiation therapy (SIRT) for the treatment of liver malignancies requires CE-CT for the delineation of the tumoral tissues, perfused liver lobe and organs at risk towards personalized dosimetry. 3 Artificial intelligence (AI) and particularly deep learning has shown very promising performance in multiple tasks, including image segmentation, [4][5][6] image generation, 7,8 dosimetry, [9][10][11] and classification. 12,13 However, the number of clean and reliable data available is still the bottle neck for generalizability and robustness of deep learning models.…”
Section: Introductionmentioning
confidence: 99%